2020
DOI: 10.1099/mic.0.000878
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm activity in the culture supernatant of a marine Pseudomonas sp. bacterium

Abstract: In the marine environment, most solid surfaces are covered by microbial biofilms, mainly composed of bacteria and diatoms. The negative effects of biofilms on materials and equipment are numerous and pose a major problem for industry and human activities. Since marine microorganisms are an important source of bioactive metabolites, it is possible that they synthesize natural ecofriendly molecules that inhibit the adhesion of organisms. In this work, the antibiofilm potential of marine bacteria was investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 74 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…IV2006 SNIV2006 decreased biofilm formation and adhesion in Flavobacterium sp. II2003 without killing or suppressing growth ( Doghri et al, 2020 ). Christofi et al (2019) reported that E. coli can colonize the gut of healthy mice and protect them against intestinal colonization by P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…IV2006 SNIV2006 decreased biofilm formation and adhesion in Flavobacterium sp. II2003 without killing or suppressing growth ( Doghri et al, 2020 ). Christofi et al (2019) reported that E. coli can colonize the gut of healthy mice and protect them against intestinal colonization by P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%